Use of del nido cardioplegia versus St. thomas solution 2 in adult mitral valve replacement surgery at a tertiary care hospital in Kolkata, India - Datta, Swarnendu; Chakrabarty, Ushnish; Podder, Tanmoy; Mukherjee, Plaban (International Journal of Research in Medical Sciences, 2020)
Background: del Nido cardioplegia has been historically used in paediatric cardiac surgery. However it’s use in adults has also been documented. It has the advantage of 90 minutes of cardiac inactivity over St. Thomas solution no.-2, which requires repeated dosing at 20 minutes interval. Aim of this study to find out whether del Nido cardioplegia with longer duration of arrest is advantageous over St. Thomas solution no. 2 in adult mitral valve replacement. Methods: Total 60 patients of severe mixed mitral valve disease of comparable patient profiles, underwent mitral valve replacement with preservation of anterolateral and posteromedial chordae. Half the patients received del Nido cardioplegia and other half received St. Thomas solution no 2. (ST-2). The two groups were compared. Results: del Nido group had lesser CPB time (70.73±12.15min) as compared to ST-2 group (81.76±20.03min) with p=0.01 ; lesser Cross clamp time (del Nido- 68.8±10.64min; ST-2- 75.83±14.00min) with p=0.02; lesser time taken to arrest heart (del Nido- 21.58±13.37 sec; ST-2- 25.26±5.27 sec) with p=0.04 & lesser time taken for normal ECG activity to manifest after release of cross clamp (del Nido- 19.86±6.10 min; ST-2- 31.03±5.28min) with p=0.02. All other parameters did not reach statistical significance. Conclusions: del Nido cardioplegia group of patients required significantly less CPB time; Cross-clamp time; Mean time taken to arrest the heart; as well as that taken to manifest normal ECG morphology when compared to ST-2 group.